2021
DOI: 10.1111/jocd.14179
|View full text |Cite
|
Sign up to set email alerts
|

Temporal augmentation using autologous fat grafting in Chinese women: Effect on temporal hairline

Abstract: Temple volume plays an important role in facial symmetry and youthfulness. The temple can be considered a transitional subunit between the forehead and the cheek and between the temporal hairline and the lateral orbit. 1 Progressive aging causes a dramatic loss of the temple's fullness, 2 greatly impacting facial appearance.Therefore, temporal augmentation is an important aspect of facial rejuvenation. It aims to achieve an appropriate fullness in the temple and a smooth facial contour of the upper face. 3 In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…All measurements were collected using Adobe Photoshop CC 2019 (Adobe Systems, Inc., San Jose, CA). The following anthropometric measurements were evaluated according to Diao et al ( 10 ), as summarized in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All measurements were collected using Adobe Photoshop CC 2019 (Adobe Systems, Inc., San Jose, CA). The following anthropometric measurements were evaluated according to Diao et al ( 10 ), as summarized in Figure 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Contrastingly, layer 4, the loose areolar tissue/parotid-temporal fascia of the temple, encompasses one sentinel vein and several perforator vessels but is otherwise predominately avascular ( 15 , 16 ), so it was considered to be an optimal injection site. Prior studies of temporal hollowing augmentation suggested placing fat grafts into both layer 2 and layer 4 ( 10 , 14 ). This strategy can be effective, but novice surgeons could have difficulty in precisely injecting fat grafts into layer 2.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of Baek et al (2009) 13 and McNichols et al (2012) 14 met most of the inclusion criteria, but their full texts were unavailable. The majority (67%) of studies included in our systematic review were original articles, 3,10,15‐27 25% were case reports or series, 28‐33 one was a technical note, 34 and one was a featured operative technique 35 . The countries of origin included the United States (25%), China (25%), South Korea (21%), and Norway (8%), and one study each from the United Kingdom, Sweden, Japan, Canada, and Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven publications discussed a classification system (Table 2). These included the visual analogue scale (VAS) 15,17,25 (27%), the hollowing severity rating scale system 15,36 (18%), the Whittaker classification 18,23 (18%), the Allergan Temple Hollowing Scale 21 (9%), the Temporal Hollowing Scale 19 (9%), and the Temporal Hollowing Aesthetic Evaluation Criteria 24 (9%). Some classified according to imaging findings 26 (9%) and some according to the pinch between the examiner's thumb and index finger 20 (9%).…”
Section: Resultsmentioning
confidence: 99%